Dynamic Impact of Stokvel Savings and Banking Sector Size in South Africa: an ARDL Approach - Lindiwe Ngcobo (Universitas Islam Negeri (UIN) Walisongo Semarang, 2026)
Purpose - The study examined the impact stokvel savings and banking sector size using ARDL bound test approach to cointegration. Method - Using quarterly time series secondary data ranging from 2009Q4 to 2020Q2. Data were subjected to unit root analysis to ensure that they were integrated of order zero (I(0)) before regressing the variables in the specified models. Result - The F-statistic value for the linear ARDL and the asymmetric ARDL, bounds test result shows evidence of cointegration among dependent variables because the computed asymmetric ARDL F-statistic values exceed the tabulated value of the upper bound at the 5% level of significance. Therefore, there is no cointegration between the dependent and the independent variables. Therefore, the study failed to reject the null hypothesis of no cointegration amongst the variables in the lower bound. The negative coefficient of the ECT(-1) shows that the relationship between stock savings and banking sector size are cointegrated. It is evident that there is an inconclusive debate on the drivers of banking sector’s size. Implication - This study contributes to this debate by introducing variable, stokvel savings. A similar study can be conducted with inclusion of all banks that make up the banking sector and their impact on South Africa’s economic growth. Originality - The objective of the study examined the impact of stokvel savings and banking sector size using ARDL bound test approach to cointegration. Keywords: Stokvel savings, Banking sector size, Gross domestic product, Money supply, ARDL, South Africa